Lithium in felsic magmas: a volcanological perspective - Dupont de Dinechin, Maylis; Balcone-Boissard, Hélène; Martel, Caroline; Rusiecka, Monika (Frontiers in Earth Science, 2023)
Volcanic eruptions are unpredictable phenomena that pose a challenge to crisis management, owing to the fact that contrasted eruptive styles (explosive versus effusive) exhibited at the surface depend on unobservable deep processes occurring in the reservoir and the volcanic conduit. Constricting degassing during magma ascent, in particular, allows for a clearer understanding of the relationships between petrological and volcano monitoring signals, and hence a better description of the volcanic hazard. To this aim, lithium (Li) has been used to track magmatic and post-eruptive processes, as a geospeedometer for processes operating on short time scales due to its high mobility in silicate melts and crystals. Yet, the accurate use of Li to assess syn-and post-eruptive processes still lack complete dataset.We propose a review of our current knowledge on Li behavior, with an emphasis on felsic (andesitic to rhyolitic) magmas whose explosive behavior during volcanic eruptions is still poorly understood.We present current knowledge regarding the Li concentration and isotopic compositions, intracrystalline diffusion, and crystal-melt-fluid partition coefficients discovered in felsic magmas and primary crystals. We describe difficulties in interpreting Li data to investigate the differentiation, degassing, ascent rate, volatile fluxing, and cooling of magmas. Finally, we suggest future directions for expanding our understanding of Li behavior.